PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMP - Sri Yulianti (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
This study aims to determine the influence of realistic mathematics education (RME) model learning on the achievements of mathematics students in grade VII at SMP Ba'it Al-Quran Kayuagung school year 2019/2020. The research method is quasi experiment. The research samples are grade VII Cairo and class VII Mecca using the study population. The data is collected by written test which is essay test.  To analyze the data, a prerequisite test of normality and homogeneity was conducted and a hypothesis test was conducted, namely the t-test. The results showed that the final test score at 0.000 and t-count was greater than the t-table. In other words, H0 is rejected. which means realistic mathematics education (RME) approach affects the achievements of mathematics learning students of SMP Ba'it Al-Quran Kayuagung. In conclusion, there are differences in learning achievement between students who use realistic mathematics education approach and students who use Teacher Centered approach.